2013
DOI: 10.1021/ic400478d
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Dinuclear Cationic Iridium(III) Complexes Bearing a 2,5-Dipyridylpyrazine (2,5-dpp) Ligand

Abstract: The synthesis, X-ray structures, photophysical, and electrochemical characterization of mono- (1) and dinuclear (2) cationic iridium(III) complexes bearing a 2,5-dipyridylpyrazine (2,5-dpp) ancillary ligand are reported. Upon the complexation of a first equivalent of iridium, the photoluminescence shifts markedly into the deep red (λem = 710 nm, ΦPL = 0.9%) compared to other cationic iridium complexes such as [Ir(ppy)2(bpy)]PF6. With the coordination of a second equivalent of iridium, room temperature luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 114 publications
4
64
0
Order By: Relevance
“…5 Å. 23,26,27,32,34,40,47 (It is noteworthy that with [Ir(ppy) 2 µ-Cl] 2 -type complexes where the Ir-Ir distances are <4 Å only the less sterically congested rac ΔΔ/ɅɅ diastereomers have been reported to date [15][16][17][18]39,[48][49][50][51][52][53][54][55] ). For 13-16 the diastereomers were separated by fractional crystallization, silica column chromatography, or a combination of the two techniques.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…5 Å. 23,26,27,32,34,40,47 (It is noteworthy that with [Ir(ppy) 2 µ-Cl] 2 -type complexes where the Ir-Ir distances are <4 Å only the less sterically congested rac ΔΔ/ɅɅ diastereomers have been reported to date [15][16][17][18]39,[48][49][50][51][52][53][54][55] ). For 13-16 the diastereomers were separated by fractional crystallization, silica column chromatography, or a combination of the two techniques.…”
Section: Synthesismentioning
confidence: 99%
“…1, 2 and 3 ( Figure 1). [18][19][20][21][22][23][24][25][26][27][28][29] Consequently, for luminescence applications research has primarily concentrated on monoiridium complexes. 30,31 Nevertheless, the study of phosphorescent diiridium complexes is a rapidly expanding topic and a range of complexes with various conjugated bridging ligands have been reported to possess efficient photo-(PL) and electroluminescence (EL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] They are synthetically versatile,a llowing facile tuningo ft he emission color via modification of the cyclometalating (C^N) and/or ancillary ligand structure. [30][31][32] Severale xamples of polynuclear cyclometalated iridiumc omplexes have been reported recently, [33][34][35][36][37][38][39] as well as some supramolecular structures where cyclometalated iridium is combinedw ith another photoactive metal complex. [15,[40][41][42][43][44][45][46] Relevant to the presentm anuscript,t here are af ew multimetallicc ompounds [15][16][17] involving cyclometalated iridiump artnered with Pt II bis-acetylide complexes,t he latter being anotherw ell-knownc lass of phosphorescent organometallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38] Herein, we designed and synthesized a series of 20 new dinuclear iridium(III) complexes (Ir1-Ir7, Scheme 1) as mitochondrial probes. Confocal fluorescence microscope and inductively coupled plasma mass spectrometry (ICP-MS) analyses demonstrated that complexes Ir2-Ir7 entered live cells through an endocytosis pathway and lighted up mitochondria 25 specifically.…”
Section: Introductionmentioning
confidence: 99%